Menggagas Tolok Ukur Pendelegasian Pengaturan Lanjutan dari Undang-Undang terhadap Peraturan-Peraturan Presiden - Safrin, Mohamad; Imran, Imran (Amsir Law Journal, 2023)
The lack of clarity regarding the relationship between position and content material for government regulations and presidential regulations can be seen in the provisions of Article 12 and Article 13 of Law Number 12 of 2011 concerning Formation of Legislation. From these provisions it can be seen that the material content of presidential regulations is broader than the content material of government regulations. From the explanation regarding the contents of government regulations and presidential regulations, it does not explicitly delegate further arrangements, there are no benchmarks for using government regulations or presidential regulations. This means that in this condition there is a similarity in the content of government regulations and presidential regulations. This research was conducted using a juridical-normative approach, research with reference to juridical aspects. This method is carried out through literature studies on various literature related to legal theories and principles. The results of this study indicate that there are inconsistencies in the position of presidential regulations, especially when juxtaposed with government regulations when viewed from the perspective of the material content. ___ Referensi Buku dengan penulis: Asshiddiqie, Jimly. (2014). Perihal Undang-Undang. Depok: Rajagrafindo Persada. Astawa, I Gede Pantja., dan Na’a, Suprin. (2012). Dinamika Hukum dan Ilmu Perundang-Undangan. Bandung: Alumni. Philipus M. Hadjon, dkk. (1993). Pengantar Hukum Administrasi Indonesia (Introduction to the Indonesian Administrative Law). Yogyakarta: Gajah Mada University Press. Soekanto, Soerjono., dan Mamudji, Sri. (2001). Penelitian Hukum Normatif: Suatu Tinjauan Singkat. Jakarta: PT Radja Grafindo Persada. Soiman. (2020). Pembentukan Peraturan Perundang-undangan Negara di Indonesia. Yogyakarta: UII Press. Artikel jurnal: Abdullah, A. G. (2018). Pengantar Memahami Undang-Undang Tentang Pembentukan Peraturan Perundang-undangan. Jurnal Legislasi Indonesia, 1(2), 1-10. Adhayanto, O. (2014). Perkembangan Sistem Hukum Nasional. Jurnal Ilmu Hukum, 5(2), 163-171. Aditya, Z. F., & Winata, M. R. (2018). Rekonstruksi Hierarki Peraturan Perundang-Undangan di Indonesia (Reconstruction of the Hierarchy of Legislation in Indonesia). Negara Hukum: Membangun Hukum untuk Keadilan dan Kesejahteraan, 9(1), 79-100. Busthami, D. (2017). Kekuasaan Kehakiman Dalam Perspektif Negara Hukum di Indonesia. Masalah-Masalah Hukum, 46(4), 336-342. Hadinatha, M. F. (2022). Penataan Materi Muatan Peraturan Pemerintah dan Peraturan Presiden dalam Sistem Hukum Indonesia. Jurnal Legislasi Indonesia, 19(2), 133-147. Husen, A. (2019). Eksistensi Peraturan Presiden dalam Sistem Peraturan Perundang-undangan. Lex Scientia Law Review, 3(1), 69-78. Muntoha, M. (2016). Pendidikan dalam Perspektif Hukum. Madaniyah, 6(1), 90-107. Siswanto, H. (2011). Memaksimalkan Prolegnas dan Prolegda dalam Politik Hukum Nasional (Politik Hukum Penanggulangan Kejahatan Perdagangan Orang di Era Globalisasi). Fiat Justisia: Jurnal Ilmu Hukum, 5(2). 190-208. Tutik, T. T. (2013). Analisis Kedudukan dan Status Hukum Ketetapan MPR RI Berdasarkan Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-Undangan. Jurnal Hukum Ius Quia Iustum, 20(1), 1-20.